2021
DOI: 10.1002/acn3.51350
|View full text |Cite
|
Sign up to set email alerts
|

Persistent neurologic symptoms and cognitive dysfunction in non‐hospitalized Covid‐19 “long haulers”

Abstract: Objective Most SARS‐CoV‐2‐infected individuals never require hospitalization. However, some develop prolonged symptoms. We sought to characterize the spectrum of neurologic manifestations in non‐hospitalized Covid‐19 “long haulers”. Methods This is a prospective study of the first 100 consecutive patients (50 SARS‐CoV‐2 laboratory‐positive (SARS‐CoV‐2+) and 50 laboratory‐negative (SARS‐CoV‐2‐) individuals) presenting to our Neuro‐Covid‐19 clinic between May and November 2020. Due to early pandemic testing limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
551
5
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 523 publications
(692 citation statements)
references
References 62 publications
42
551
5
22
Order By: Relevance
“…The Corona pandemic has led to dramatic changes in social and economic life worldwide. In addition to the high number of COVID-19-related dead, those who are seriously ill, and patients who are suffering from long/post COVID [1] , [2] , the general population is also affected by the way in which the dramatic pandemic measures have influenced psychosocial relations and daily living. All of these issues point toward the urgent need for vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The Corona pandemic has led to dramatic changes in social and economic life worldwide. In addition to the high number of COVID-19-related dead, those who are seriously ill, and patients who are suffering from long/post COVID [1] , [2] , the general population is also affected by the way in which the dramatic pandemic measures have influenced psychosocial relations and daily living. All of these issues point toward the urgent need for vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…[113][114][115][116] Graham et al have reported on a group of 50 SARS-C0V-2 patients who were seen in the Neuro-COVID-19 Clinic at Northwestern University who were "long haulers." 117 The main neurologic symptoms were "brain fog," headache, numbness/tingling, dysgeusia, anosmia, myalgias, dizziness, pain, blurred vision, tinnitus, and dysgeusia in frequencies ranging from 81% for "brain fog" to 29% for tinnitus. Dys-or ageusia, which are specially common, appear to be attributable to the expression of ACE-2 receptors on Type II taste receptor cells in the fungiform papillae of the tongue.…”
Section: Brain and Peripheral Nervousmentioning
confidence: 99%
“…Subsequent evidence emerged that persistent symptoms are common for both hospitalized (3) and non-hospitalized (4) cohorts, and these patients have described challenges with stigma as well as difficulty accessing care for their symptoms (5). Later reports indicate disruption to usual activities and impaired quality of life may last months (68). Studies of survivors of severe acute respiratory syndrome (SARS) hospitalized from 2001-2003 showed persistent pulmonary dysfunction (9) as well as chronic fatigue and psychiatric illnesses (10) lasting years.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 47,910 patients found the most frequent symptoms include fatigue, headache, attention disorder, hair loss, and dyspnea (22) and noted a high degree of heterogeneity in published studies with a need for future studies to stratify results by patient baseline characteristics and disease severity. Individual cohort studies have reported a variety of specific risk factors for prolonged symptoms including female sex (2325), higher body mass index (BMI) (23,24), middle age (26), older age (24,27), underlying autoimmunity (8), while one study found no significant predictors (28). Features of acute COVID-19 may predict PASC, with cohort studies finding increasing risk for: patients with more than 5 acute symptoms (24), presence of specific acute symptoms (chest pain, fatigue, fever, olfactory impairment, headaches, or diarrhea) (25), and hospitalization (26).…”
Section: Introductionmentioning
confidence: 99%